Analysis of the Development of Micro, Small and Medium Enterprises (MSME) at the Gowa Regency Industry and Trade Service - Andi Hakib; Asdar; Zulfikram (Jurnal Ekonomi Balance, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting regional economic growth, employment generation, and poverty reduction. However, many MSMEs continue to face structural challenges related to limited access to capital, inadequate managerial capabilities, weak marketing networks, and technological constraints. This study aims to analyze the effectiveness of MSME development programs implemented by the Department of Industry and Trade of Gowa Regency and identify the key factors influencing their implementation. A qualitative descriptive approach was employed using in-depth interviews, direct observation, and document analysis. Data were collected from government officials and selected MSME owners and analyzed through the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that the department has implemented various development strategies, including entrepreneurship training, business mentoring, product promotion, marketing facilitation, business legality assistance, and technology support. These initiatives have contributed to improving entrepreneurial knowledge, managerial capacity, and market accessibility among MSME actors. Nevertheless, the effectiveness of these programs remains constrained by limited dissemination of information, unequal access to government support, insufficient digital competencies, inadequate financial literacy, and restricted access to business financing. The study demonstrates that sustainable MSME development requires stronger collaboration between government institutions, financial organizations, universities, and private-sector stakeholders to strengthen entrepreneurial capacity and business competitiveness. This research contributes to the MSME development literature by emphasizing that government intervention should be integrated with continuous capacity building, digital transformation, and institutional collaboration to achieve sustainable regional economic development.